دور التخطيط الاستراتيجي في تحسين الأداء المؤسسي - نورالدين, دحماني; نصر, زايد; محمد, رقيق (جامعة الوادي - University of Eloued, 2023)
" التخطيط الاستراتيجي من المواضيع الإدارية الهامة جدا والتي تشغل أذهان كل المدراء ورجال الأعمال،لكونهم يدركون جيدا بان الحكمة والخبرة وحدهما ليستا كافيتين لتطوير مؤسساتهم في هذا العالم المعاصر المتجدد. وقد إعتمدنا في دراستنا على عينة مكونة من 30 موظف من مختلف المستويات في المؤسسة، حيث تم توزيع الاستبيانات على موظفي المؤسسة ومن ثم تم جمع المعلومات الشخصية، حيث أنها تحتوي على محورين رئيسيين: التخطيط الاستراتيجي والأداء. حيث توصلنا إلى عدة نتائج أهمها: - أن هناك علاقة بين كل من الرؤية الإستراتيجية والأهداف الإستراتيجية والبيئة الداخلية والخارجية والأداء في شركة الاتصالات الجزائرية. - ومن جهة اخرى يوجد استجابة مرتفعة للموظفين على استبانة التخطيط الاستراتيجي بأبعاده والأداء في المؤسسة. " Strategic planning is considered one of the very important administrative topics that occupy the minds of all managers and businessmen, because they are well aware that wisdom and experience alone are not sufficient to develop their institutions in this modern and renewed world. In our study, we relied on a sample of 30 employees from various levels in the organization, where the questionnaires were distributed to the organization's employees, and then personal information was collected, as it contains two main axes: strategic planning and performance. We reached several results, the most important of which are: - That there is a relationship between each of the strategic vision and strategic objectives and the internal and external environment and performance in the Algerian Telecom Company. - On the other hand, there is a high response of employees to the strategic planning questionnaire with its dimensions and performance in the institution.
Keywords: التخطيط الاستراتيجي/الأداء/ الرؤية الاستراتيجية.; strategic planning / performance / strategic vision.